2018
DOI: 10.3390/en11030508
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Biodegradable Electro-Insulating Liquid and Its Subsequent Modification by Nanoparticles

Abstract: Abstract:The paper is focused on the possibility of replacing petroleum-based oils used as electro-insulating fluids in high voltage machinery. Based on ten years of study the candidate base oil for the central European region is rapeseed (Brassica napus) oil. Numerous studies on the elementary properties of pure natural esters have been published. An advantage of natural ester use is its easy biodegradability, tested according to OECD-301D (Organisation for Economic Co-operation and Development) standard, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…On the other hand, the behavior of dispersed conductive fillers is very-well known [45,46,47,48] and percolation threshold could be estimated based on the significant increase of conductivity. However, the dielectric parameters of basic material could be improved by addition of relatively low amount of nanofiller, as is evident from our previous studies [49,50,51]. In connection with these claims, the study [52] describes a theory of percolation and interfacial characterisation via breakdown voltage measurement.…”
Section: Improvement Of Epoxy Based Composites Insulating Propertiesmentioning
confidence: 91%
“…On the other hand, the behavior of dispersed conductive fillers is very-well known [45,46,47,48] and percolation threshold could be estimated based on the significant increase of conductivity. However, the dielectric parameters of basic material could be improved by addition of relatively low amount of nanofiller, as is evident from our previous studies [49,50,51]. In connection with these claims, the study [52] describes a theory of percolation and interfacial characterisation via breakdown voltage measurement.…”
Section: Improvement Of Epoxy Based Composites Insulating Propertiesmentioning
confidence: 91%
“…In the case of nanofluids' applications in transformers, the main research is related to the improvement of the dielectric properties of the base liquids. There are many publications confirming the positive influence of electro-insulating liquids' modifications, with nanomaterials on their dielectric properties and phenomena such as breakdown voltage [40][41][42][43], streamer propagation [44], electrical conductivity, and the dissipation factor [45][46][47][48][49]. In addition, as reported in the literature [50,51], fullerene C 60 can also be used to absorb free radicals arising from the aging of vegetable oils.…”
Section: Introductionmentioning
confidence: 88%
“…Analyzing the calculated temperature decreases, it can be concluded that the modification of electro-insulating liquids with surfactant Span ® 20 and titanium dioxide TiO 2 nanoparticles does not significantly affect the heat transport in the obtained nanofluids. Bearing in mind that these nanoparticles are mainly used to improve dielectric properties [41,46,49], it can be concluded that they will not cause deterioration in the cooling efficiency of the device.…”
Section: Kind Of Liquidmentioning
confidence: 99%
“…Articles [2,3] are in the lines of modifying the properties of insulating fluids using suitable nanoparticles. In [2], an attempt has been made by Mentlik et al to improve the properties of the natural ester available in the Central European region that is a rapeseed (Brassica napus seed) oil.…”
Section: A Review Of the Special Issuementioning
confidence: 99%
“…Articles [2,3] are in the lines of modifying the properties of insulating fluids using suitable nanoparticles. In [2], an attempt has been made by Mentlik et al to improve the properties of the natural ester available in the Central European region that is a rapeseed (Brassica napus seed) oil. Authors tried to modify the properties of natural esters through percolation treatment and oxidation inhibition by a phenolic-type inhibitor and further using titanium dioxide (TiO 2 ) nanoparticles with a silica surface treatment.…”
Section: A Review Of the Special Issuementioning
confidence: 99%